Quantitative ultrasound and photoacoustic assessments of red blood cell aggregation in the human radial artery - Taehoon Bok; Eno Hysi; Michael C. Kolios (Photoacoustics)
We develop concurrent US and photoacoustic (PA) imaging to characterize structural/physiological impact of in-vivo red blood cell (RBC) aggregation. PA images at 700/800/900 nm were collected from the radial arteries of 12 participants across age groups (20 s/30 s/40 s) alongside US images (21 MHz, VevoLAZR). RBC aggregate size was estimated from US-derived structure-factor-size-estimation (DSFSE) and PA-derived spectral-slope (SS), along with oxygen saturation (sO2). At peak systole (PS), DSFSEPS and SSPS approximated 1 RBC and −0.1 dB/MHz, respectively, across all ages, with sO2PS values of 97.1 %, 94.7 %, and 93.0 % for each group. At end diastole (ED), DSFSEED, SSED and sO2ED values were 2.6, 3.4, and 4.7 RBCs; −0.7, −0.9, and −1.2 dB/MHz; and 98.7 %, 97.2 %, and 96.7 %, respectively. Differences between SSED and SSPS (δSS) and sO2ED and sO2PS (δsO2) increased with age, indicating aging-related increases in DSFSE and δSS, as well as decreases in sO2PS and sO2ED.